Evaluation of the fermentation in the diphtheric toxin production (1998)
This study was developed to find out the technological feasibility of fermentation culture of Corynebacterium diphtheriae in a bioreactor for production of diphtheric toxin. The fermentation process was studied in a 5L New Brunswick biorreactor. The following parameters were measured: biomass production, substrate consumption, toxin production, dissolved oxygen and pH variation during fermentation. The following indicators of the fermentation process were calculated: biomass/substrate, toxin/substrate, toxin/biomass, toxin produced/hour (productivity). C. diphtheriae PW8 79 LA11 strain was used. The composition of the growth media was: 4L of Muller- Stainer medium, 0,5% inoculum,1,7% maltose, 0,3% phosphate, 1,25% calcium chloride. The conditions of incubation were: 35C, 48 hours, agitation at 900 rpm and aereation 1 VVM. The results showed that biomass production levels occurred between 24 and 36 hours of fermentation. Substrate consumption, toxin production and a pH increased simultaneously. It was concluded that fermentation is a useful process for the production of diphtheric toxin compared to the traditional static system. Fermentation is easier to control and the same yield of toxin is obtained in 48 hours instead of 168 hours in the static system.